Interleukin-1/toll-like receptor-induced nuclear factor kappa B signaling participates in intima hyperplasia after carotid artery balloon injury in goto-kakizaki rats: a potential target therapy pathway. - Xiaotian Zhang (Public Library of Science (PLoS), 2014)
The value of restenosis after percutaneous coronary intervention (PCI) is recognized worldwide, especially for diabetic patients. Interleukin-1/Toll-like receptor (IL-1/TLR) signaling is involved in innate and adaptive immune responses, but whether and how the IL-1/TLR-induced nuclear factor kappa B (NFκB) pathway plays key roles in intimal formation is unclear. The underlying mechanism of intima hyperplasia was investigated with a model of carotid balloon injury in Goto-Kakizaki (GK) and Wistar rats and with lipopolysaccharide-stimulated macrophages. Elastic-van Gieson staining showed the medial area peakedon Day 3 post-injury and decreased by Day 7 post-injury in both GK and Wistar rats. The N/M at Day 7 in GK rats was significantly higher than in Wistar rats (p<0.001). The percent of 5-ethynyl-2'-deoxyuridine (EdU) staining-positive cells on Day 3 post-injury was greater than seen on Day 7 post-injury in GK and Wistar rats. The percent of EdU-positive cells on Days 3 and 7 post-injury in Wistar rats was less than that found in GK rats (p<0.01; p<0.05). NFκBp65 immunostaining had increased by Day 7 post-injury. Agilent Whole Genome Oligo Microarray verified that the IL-1/TLR-induced NFκB pathway was activated by carotid balloon injury. TLR4, IL-1 receptor associated kinase, inhibitors α of NFκB, human antigen R, c-Myc (Proto-Oncogene Proteins), EGF-like module-containing mucin-like hormone receptor-like 1 and Interleukin-6 were up-regulated or down-regulated according to immunochemistry, quantitative real-time PCR, Western blotting and Enzyme linked immunosorbent assay. Overall, we conclude that the IL-1/TLR-induced NFκB pathway participates in the intimal hyperplasia after carotid injury in GK and Wistar rats and that GK rats respond more intensely to the inflammation than Wistar rats.